2001
DOI: 10.1097/00005537-200102000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Interferon‐γ, Interleukin‐4, and Interleukin‐12 Cytokine Levels in Anti‐Histamine Type 2–Treated Allergic Rhinitis Patients

Abstract: H2 antagonists probably induce their effects by enhancing the amount of IFN-gamma and by reducing IL-4 cytokines, which, respectively, induce a decrease and an increase in the IgE synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…T cells playa critical role in controlling immune responses and they are involved in the inflammatory processes characteristic of allergic diseases. Based on their cytokine production profile helper, T cells (T h) are generally distinguished into two distinct subsets: ThI cells producing IL-2 and IFN-y and T h2 cells producing IL-4, IL-5, IL-6, IL-10, IL-I3 (16)(17). Several studies investigated the cytokine mRNA expression and protein production profiles (ThI versus Th2) of T cell clones and of peripheral mononuclear cells of allergic patients (10,(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T cells playa critical role in controlling immune responses and they are involved in the inflammatory processes characteristic of allergic diseases. Based on their cytokine production profile helper, T cells (T h) are generally distinguished into two distinct subsets: ThI cells producing IL-2 and IFN-y and T h2 cells producing IL-4, IL-5, IL-6, IL-10, IL-I3 (16)(17). Several studies investigated the cytokine mRNA expression and protein production profiles (ThI versus Th2) of T cell clones and of peripheral mononuclear cells of allergic patients (10,(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies (17,21) have shown that cytokine production is modified during anti-allergy treatments (histamine antagonist, Chinese herbs) and by immunotherapy; however the effect of therapy on cytokine production has been the subject of much debate and is still unclear. H2 antagonists have been shown to induce their effects by enhancing the amount of IFN-y and by reducing IL-4 (17). Decrease in IL-4 serum level following immunotherapy with no significative increase in IFN-y was reported (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But it did not inhibit the Th1 cytokines such as IL-2 and IFN-␥. 27 Testa et al 28 determined a clear-cut clinical improvement in patients with allergic rhinitis with the use of H2 blockers. They suggested that H2 blockers increased IFN-␥ levels, but decreased IL-4 and total IgE levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hussein et al (10) showed that polymorphisms of Toll-like receptors 2 (TLR-2) and TLR-4 genes were associated with susceptibility to AR. Furthermore, Testa et al (11) showed that the variation in interleukin 4 (IL-4) gene expression determined the severity of AR. In addition, the variation in ILs gene expression have also been associated with the severity of AR (12,13).…”
Section: Introductionmentioning
confidence: 99%